2020
DOI: 10.1111/and.13929
|View full text |Cite
|
Sign up to set email alerts
|

ATPase inhibition by omeprazole reveals role of heat shock proteins on testicular torsion

Abstract: Testicular torsion is an important urological condition which is often seen in young males (between 12-18 years of age) but it can occur at any ages, even newborns and before birth. Testicular torsion usually requires emergency surgery, and the survival of testis can be achieved with surgery within 6-8 hr. However, prolonged cases may result in the death of the testis and surrounding tissues. Furthermore, torsion can decrease spermatogenesis and induce infertility (Moore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… [ 133 ] Rat model Suture 5 h Scrotual incisions 5 h Quercetin 4 h 20 min post ischemia Intraperitoneal 15 mg/kg Quercetin improved I/R- induced histopathological damage, increased immunoexpression of testicular eNOS and germ cell apoptosis. Anti-thrombotic Rat model Scrotal fixation with suture 3 h and 6 h Scrotal incision 7 day Enoxaparin and alteplase At reperfusion Enoxaparin: subcutaneous; Alteplase: intravenous 200 IU/kg of enoxaparin and 0.9 mg/kg alteplase Enoxaparin and alteplase↑ testicular weight, inhibin level, redox balance and testicular histoarchitecture Anti-Ulcer [ 134 ] Rat model Scrotal fixation with suture 3 h Scrotal incision 2 h Famotidine I hr pre-ischemia Oral 20 mg/kg Famotidine ↓ testicular DNA damage, ↑ spermatogenesis and antioxidant activities [ 135 ] Rat model Scrotal fixation with suture 2 h Scrotal incision 3 days Omeprazole At reperfusion, then once per day for another 2 days Oral 0.02 mg/kg Omeprazole ↓ MDA, MPO, 8OHdG, HSP40, HSP70, HSP90 Cysteine Protease [ 136 ] Rat model …”
Section: Pharmacological Potentials In the Management Of I/r Injurymentioning
confidence: 99%
See 1 more Smart Citation
“… [ 133 ] Rat model Suture 5 h Scrotual incisions 5 h Quercetin 4 h 20 min post ischemia Intraperitoneal 15 mg/kg Quercetin improved I/R- induced histopathological damage, increased immunoexpression of testicular eNOS and germ cell apoptosis. Anti-thrombotic Rat model Scrotal fixation with suture 3 h and 6 h Scrotal incision 7 day Enoxaparin and alteplase At reperfusion Enoxaparin: subcutaneous; Alteplase: intravenous 200 IU/kg of enoxaparin and 0.9 mg/kg alteplase Enoxaparin and alteplase↑ testicular weight, inhibin level, redox balance and testicular histoarchitecture Anti-Ulcer [ 134 ] Rat model Scrotal fixation with suture 3 h Scrotal incision 2 h Famotidine I hr pre-ischemia Oral 20 mg/kg Famotidine ↓ testicular DNA damage, ↑ spermatogenesis and antioxidant activities [ 135 ] Rat model Scrotal fixation with suture 2 h Scrotal incision 3 days Omeprazole At reperfusion, then once per day for another 2 days Oral 0.02 mg/kg Omeprazole ↓ MDA, MPO, 8OHdG, HSP40, HSP70, HSP90 Cysteine Protease [ 136 ] Rat model …”
Section: Pharmacological Potentials In the Management Of I/r Injurymentioning
confidence: 99%
“…Famotidine also preserved testicular histo-morphology [ 134 ]. In another experimental study, Güney et al [ 135 ] revealed that omeprazole, a proton pump inhibitor, significantly reduced lipid peroxidation (as depicted by reduced MDA), oxidative DNA injury (evidenced by reduced (8OHdG), neutrophil accumulation (evidenced by reduced myeloperoxidase activity), and HSP40, HSP70, and HSP90. Güney et al [ 135 ] also showed that omeprazole attenuated torsion/detorsion-induced distortion of testicular histoarchitecture.…”
Section: Anti-diabeticsmentioning
confidence: 99%